Parallel Mechanism Composed of Abdominal Cuticles and Muscles Simulates the Complex and Diverse Movements of Honey Bee (Apis mellifera L.) Abdomen. Issue 5 (24th October 2020) - Liang, Youjian; Meng, Kuilin; Zhao, Jieliang; Ren, Jing; Ge, Siqin; Yan, Shaoze
Abstract: The abdominal intersegmental structures allow insects, such as honey bees, dragonflies, butterflies, and drosophilae, to complete diverse behavioral movements. In order to reveal how the complex abdominal movements of these insects are produced, we use the honey bee ( Apis mellifera L.) as a typical insect to study the relationship between intersegmental structures and abdominal motions. Microstructure observational experiments are performed by using the stereoscope and the scanning electron microscope. We find that a parallel mechanism, composed of abdominal cuticle and muscles between the adjacent segments, produces the complex and diverse movements of the honey bee abdomen. These properties regulate multiple behavioral activities such as waggle dance and flight attitude adjustment. The experimental results demonstrate that it is the joint efforts of the muscles and membranes that connected the adjacent cuticles together. The honey bee abdomen can be waggled, expanded, contracted, and flexed with the actions of the muscles. From the view point of mechanics, a parallel mechanism is evolved from the intersegmental connection structures of the honey bee abdomen. Here, we conduct a kinematic analysis of the parallel mechanism to simulate the intersegmental abdominal motions.